KEMANDIRIAN PETANI DALAM MENGADOPSI VARIETAS UNGGUL BARU (VUB) CABAI MERAH DI DESA SITU UDIK KECAMATAN CIBUNGBULANG KABUPATEN BOGOR - Neng Minanti; Wida Pradiana; Wasrob Nasruddin (Jurnal Inovasi Penelitian, 2020)
Agricultural development currently needs self reliance of farmers in adopting technologies including VUB technology. The problem that occurs in the adoption VUB of red chili at the farm level is that farmers are easily tempted by promotion agents - selling seeds of superior seeds and do not understand the origin and quality of seeds adopted. This study aims to describe the level of self reliance of farmers, analyze the factors related with the self reliance of farmers, as well as formulate appropriate strategies to support increased farmer self reliance in supporting adopting VUB of red chili. This study was conducted in Situ Udik Village, Cibungbulang District, Bogor Regency, West Java from April to July 2020. A sample of 45 farmer group members was determined using purposive sampling based on the consideration and activeness of farmer group members in the red vine mining activities. Data were processed using descriptive statistical techniques and Spearman Ranking ranking and Kendall’s W analysis. The results of the study showed that the self reliance of farmers in adopting the red chili VUB was relatively high. Factors that had a significant relationship with the self reliance of farmers in adopting the red chili VUB were formal education, non-formal education, and all capacity factors of farmer. Then, solving strategic problems is carried out by conducting extension activities and making demonstration plots as a means of supporting extension activities.